EVALUASI JUMLAH BAL DAN MUTU SENSORI DARI YOGHURTYANG DIFERMENTASI DENGAN ISOLAT Lactobacillus plantarum 1 - Yansyah, Nofendri '; ', Yusmarini '; Rossi, Evy ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The aim of the research was to obtain the best combination of various starter i.e. Lactobacillusplantarum 1 R.1.3.2, Lactobacillusplantarum1 R.11.1.2, Lactobacillus bulgaricusFNCC 0041 and Streptococcus thermophilusFNCC 0040 to produced yoghurt. The experiment research used a completely randomized design (CRD) with five treatments and four replications. The treatments were Y1: Starter 3% S. thermophilus FNCC 0040 + 3% Starter L.bulgaricus FNCC 0041, Y2 : 3% Starter S. thermophilus FNCC 0040 + 3% Starter L. plantarum 1 R.1.3.2, Y3 : Starter 3% S. thermophilus FNCC 0040+ 3% Starter L. plantarum 1 R.11.1.2, Y4 : 2% Starter S. thermophilus FNCC 0040 + 2% Starter L. bulgaricus FNCC 0041 + 2% StarterL. plantarum 1 R.1.3.2, Y5 : 2% StarterS. thermophilus FNCC 0040 + 2% StarterL. bulgaricus FNCC 0041 + 2% Starter L. plantarum 1 R. 11.1.2. Data obtained were analized using ANOVA and DNMRT at 5%. The result showed that the combination of lactic acid bacteria as a yogurt starter was significantly affected on titration acid total and lactic acid bacteria. The best yoghurt from this research was incubated using Y4 treatment 2% Starter S. thermophilus FNCC 0040 + 2% StarterL. bulgaricus FNCC 0041 + 2% Starter L.Plantarum 1 R.1.3.2 with pH value was 4.62, titration acid total 1.11%, lactic acid bacteria total 1.23×108. The best overall acceptance of yoghurt obtained at Y4 treatment. Keywords: Yoghurt, Fermentation, Lactobacillus plantarum 1.